Effects of norspermidine on Pseudomonas aeruginosa biofilm formation and eradication. Issue 3 (27th January 2016) - Qu, Lin; She, Pengfei; Wang, Yangxia; Liu, Fengxia; Zhang, Di; Chen, Lihua; Luo, Zhen; Xu, Huan; Qi, Yong; Wu, Yong
Abstract: Biofilms are defined as aggregation of single cell microorganisms and associated with over 80% of all the microbial infections. Pseudomonas aeruginosa is a Gram‐negative opportunistic pathogen capable of leading to various infections in immunocompromised people. Recent studies showed that norspermidine, a kind of polyamine, prevented and disrupted biofilm formation by some Gram‐negative bacterium. In this study, the effects of norspermidine on P. aeruginosa biofilm formation and eradication were tested. Microtiter plate combined with crystal violet staining was used to study the effects of norspermidine on P. aeruginosa initial attachment, then we employed SEM (scanning electron microscope), qRT‐PCR, and QS‐related virulence factor assays to investigate how norspermidine prevent biofilm formation by P. aeruginosa . We reported that high‐dose norspermidine had bactericide effect on P. aeruginosa, and norspermidine began to inhibit biofilm formation and eradicate 24‐h mature biofilm at concentration of 0.1 and 1 mmol/L, respectively, probably by preventing cell‐surface attachment, inhibiting swimming motility, and downregulating QS‐related genes expression. To investigate the potential utility of norspermidine in preventing device‐related infections, we found that catheters immersed with norspermidine were effective in eradicating mature biofilm. These results suggest that norspermidine could be a potent antibiofilm agent for formulating strategies against P. aeruginosa biofilm. Abstract : Norspermidine could inhibit biofi lm formation and eradicate 24‐ h mature biofi lm in Pseudomonas aeruginosa, prevent cell‐ surface attachment, and downregulate QS‐ related gene expression.